Design and optimization of simple atmospheric water generator using thermoelectric module - T. Ajiwiguna; M.R. Kirom (Universitas Mataram, 2023)
Atmospheric water generator (AWG) is a device for producing water from humid air. The water is produced by cooling the air until below its dew point temperature. This study presents the optimization of a simple thermoelectric AWG device (S-TEAWG) for emergency purposes. The designed S-TEAWG consists of a thermoelectric module and condensation plate as a cooler and condensation surface, respectively. The plate is attached to the cold side of the thermoelectric module to enhance the contact surface area with the ambient air. The thermoelectric module with the dimension of 4 cm Ãƒâ€” 4 cm is operated at 12 V of voltage and 50 oC of hot side temperature. The device is installed vertically thus the condensates flow down naturally due to gravity. Various surface areas of vertical plates, from 0.01 m2 to 0.09 m2, are evaluated theoretically to obtain the maximum water production. The results show that the lower temperature of the vertical plate is achieved at a smaller surface area. However, the optimum surface area is obtained at 0.03 m2 with 60.9 ml/d of water production.